2015
DOI: 10.1016/j.neulet.2015.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Tau facilitates Aβ-induced loss of mitochondrial membrane potential independent of cytosolic calcium fluxes in mouse cortical neurons

Abstract: Alzheimer’s disease (AD) is defined by presence of two pathological hallmarks, the intraneuronal neurofibrillary tangle (NFT) formed by abnormally processed tau, and the extracellular amyloid plaques formed primarily by the amyloid beta peptide (Aβ). In AD it is likely that these two proteins act in concert to impair neuronal function, and there is evidence to suggest that one of the key targets on which they converge is the mitochondria. For example, overexpression of a pathologic form of tau in rat primary c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…It may be that tau knock down is not sufficient (as compared to tau −/− ) to ameliorate KA-induced Ca 2+ cyt load, but this is unlikely as we achieved 84% – 90% knockdown of endogenous tau in our model. In a previous study from our lab, we found that primary cortical neurons from tau −/− mice displayed significantly enhanced Ca 2+ responses to treatment with an Aβ 42 oligomer/fibril mixture (Pallo and Johnson, 2015). We attributed this unexpected result to developmental abnormalities previously observed in tau −/− mouse neurons related to retardation of neurite outgrowth (Dawson et al, 2001), which is governed by large, frequent L-type Ca 2+ channel transients (Tang et al, 2003).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…It may be that tau knock down is not sufficient (as compared to tau −/− ) to ameliorate KA-induced Ca 2+ cyt load, but this is unlikely as we achieved 84% – 90% knockdown of endogenous tau in our model. In a previous study from our lab, we found that primary cortical neurons from tau −/− mice displayed significantly enhanced Ca 2+ responses to treatment with an Aβ 42 oligomer/fibril mixture (Pallo and Johnson, 2015). We attributed this unexpected result to developmental abnormalities previously observed in tau −/− mouse neurons related to retardation of neurite outgrowth (Dawson et al, 2001), which is governed by large, frequent L-type Ca 2+ channel transients (Tang et al, 2003).…”
Section: Discussionmentioning
confidence: 92%
“…Because we and others have found that complete ablation of tau throughout development causes neuronal abnormalities including aberrant Ca 2+ signaling in tau −/− mice and primary cultures derived from these mice (Dawson et al, 2001; Dawson et al, 2010; Pallo and Johnson, 2015), we used a knockdown approach via lentiviruses expressing tau shRNA in rat primary cortical neurons. Rat primary neurons were used in lieu of mouse primary neurons because rat cultures were better able to tolerate the lentiviral and experimental treatments.…”
Section: Resultsmentioning
confidence: 99%
“…However, the complete or partial reduction of tau expression prevents these defects without affecting the axonal transport baseline ( Vossel et al, 2010 ). Other groups describe that neurons from tau KO mice are also resistant to Aβ-induced mitochondrial damage compared to neurons obtained from WT mice ( Pallo and Johnson, 2015 ). However, tau KO neurons show a more pronounced cytosolic calcium elevation in response to Aβ, suggesting that tau may facilitate Aβ-induced mitochondrial damage in a manner that is independent of cytosolic calcium increase ( Pallo and Johnson, 2015 ).…”
Section: Tau Protein In Health and Diseasementioning
confidence: 99%
“…Other groups describe that neurons from tau KO mice are also resistant to Aβ-induced mitochondrial damage compared to neurons obtained from WT mice ( Pallo and Johnson, 2015 ). However, tau KO neurons show a more pronounced cytosolic calcium elevation in response to Aβ, suggesting that tau may facilitate Aβ-induced mitochondrial damage in a manner that is independent of cytosolic calcium increase ( Pallo and Johnson, 2015 ). Complementary studies show that tau protein interacts either directly or indirectly with more than 100 proteins in physiological conditions.…”
Section: Tau Protein In Health and Diseasementioning
confidence: 99%
“…Alzheimer's disease (AD) is characterized by presence of two pathological hallmarks, extracellular senile plaques and intracellular neurofibrillary tangles (NFTs) [3]. Senile plaques formed primarily by the amyloid beta peptide (Aβ) [4]. Tauopathies are also a group of neurodegenerative diseases characterized by the aggregation of Tau protein into filamentous lesions such as NFTs.…”
Section: Introductionmentioning
confidence: 99%